Correction: A novel SfaNI-like restriction-modification system in Caldicellulosiruptor extents the genetic engineering toolbox for this genus. - Steve Swinnen; Christian Zurek; Marco Krämer; Rebecca M Heger; Jan-Eike Domeyer; Jan Ziegler; Vitali A Svetlitchnyi; Albrecht Läufer (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0279562.].